A IMPORTÂNCIA DOS FATORES POSITIVOS NA PROTEÇÃO DA SAÚDE MENTAL E DO COMPORTAMENTO SUICIDA ENTRE CIDADÃOS DOS PAÍSES DE LÍNGUA PORTUGUESA (CPLC) - Henrique Marques Pereira; Marlene Patrícia Baptista Pestana (Sağlık Akademisi Kastamonu)
Introduction: When it comes to mental health, traditional research has been revolving around risk factors and their repercussions on mental health. On the other hand, understanding positive factors underlies prevention strategies of self-improvement of these skills, and social and clinical interventions necessary to maintain good health and well-being. Social support, self-esteem and resilience have been the focus of several studies of this scope, having been associated with better mental health outcomes and lower suicidal behaviors. Objectives: With this study, our objectives are to assess the importance of social support, self-esteem and resilience in protecting mental health and suicidal behavior, to determine differences between countries of residence, to assess levels of association between variables, as well as determining the effect of sociodemographic variables, country of residence, social support, self-esteem and resilience in predicting mental health and suicidal behavior. Method: In this study participated 1006 citizens of the Community of Portuguese Language Countries (CPLC), between 18 and 80 years of age (mean = 41.76; SD = 14.19). 40.7% of the participants lived in Brazil, 29.9% lived in the ACPOL and 29.4% were from Portugal. For this study, we included a sociodemographic questionnaire that asked about the participants’ age, country of residence, gender, sexual orientation, ethnicity, professional status, educational attainment, socioeconomic status and marital status. To identify the presence of psychological symptoms (depression, anxiety, or somatization) and thus measure participants’ mental health, we utilized the Brief Symptom Inventory-18 (BSI-18). To assess suicidal behavior, we included the Suicidal Behaviors Questionnaire – Revised (SBQ-R). To check for social support (family, friends and significant others), the Portuguese version of the Multidimensional Scale of Perceived Social Support (MSPSS) was utilized. To measure self-esteem, we utilized the Rosenberg Self-Esteem Scale (RSES). To measure resilience, we utilized the Conner-Davidson Resilience Scale–10 (CD-RISC-10). A website was created for the purpose of the investigation, to disseminate the questionnaire online through mailing lists and social media, from May to October 2021, using a convenience sample method. Results: The results showed statistically significant differences between the CPLC countries for social support, self-esteem, resilience, mental health, and suicidal behavior. The positive factors were negatively correlated with mental health and suicidal behavior. When added to sociodemographic variables, social support, self-esteem, and resilience are good predictors of both mental health and suicidal behavior. Conclusion: We concluded that, as previously shown in other studies, social support, self-esteem, and resilience all constitute protective factors for mental health and suicidal behaviors. Self-esteem took on an especially relevant role, possibly due to its moderating effect in positive life outcomes, less prevalence of psychological symptomatology and general mental well-being, since a strong sense of self-esteem is also linked to better locus of control and higher personal psychological resources to handle adversity.